(untitled) (Bulletin of criminological association of Ukraine, 2023)
Three levels of personnel support of the State Customs Service are distinguished. The first is the highest level, at which the activities of the coordination and management bodies of the State Customs Service of Ukraine, namely the Cabinet of Ministers of Ukraine and the Ministry of Finance of Ukraine, are of key importance. Within the framework of the specified level, the following is ensured: 1) formation of the general state personnel policy in the field of public service of authorities in general and the State Customs Service in particular; 2) issuance of key subordinate regulatory legal acts for the implementation of the customs legislation of Ukraine, which approve the customs policy, the basics of customs affairs and the work of executive authorities, which are authorized to implement activities in the relevant direction; 3) building the highest management level of the State Customs Service of Ukraine. The second level of staffing of the State Customs Service of Ukraine is implemented by officials of the State Customs Service directly, with the aim of consolidating the legal and organizational foundations of staffing of the State Customs Service. At this level, the following is carried out: 1) definition and implementation of the HR strategy with the personnel of the State Customs Service; 2) establishment of procedures and requirements for personnel procedures carried out in bodies and units of the State Customs Service of Ukraine; 3) improvement of staffing of the State Customs Service of Ukraine; 4) consolidation of the selection procedure for positions in bodies and divisions of the State Customs Service of Ukraine The last, the third level of personnel support of the State Customs Service of Ukraine, consists in the work of the territorial divisions of this department. This level includes: direct implementation of HR policy and Strategy; fulfillment of the requirements of the regulatory legal acts of the Head of the State Customs Service and other competent subjects of personnel support of this body; education and professional training of personnel; ensuring his service; realization by each of its representatives of their rights, freedoms and interests; control of the legality of activities of personnel units.